Evaluation of senior ICT requirement based on knowledge sharing framework - Dhillon, Sharanjit Kaur; Abdul Rahman, Azizah; Zainal Abidin, Wardah (2010)
The purpose of this study is to identify the problems faced by senior citizens while using computer and to identify the most popular computer technologies used among the senior citizens.This paper formulates some hypothesis based on a survey conducted in early 2010, where main issues were identified as requirements and opportunity of sharing knowledge among the senior citizens.Findings shows that specific computer technology requirement and suitable content of a web portal that suits senior citizens is essential so that the older generation who see computers and new technology as what they have the potential to be - a tool for expanding their horizons, learning new skills and finding new interests at any age. The limitation of this paper is identifying the ICT requirements for senior citizens. As for future research it is suggested that the study about the content of a web portal as well as the design guidelines for the portal to be analyzed.This paper provides information on barriers among senior citizens using a computer. Secondly, the website design requirement for this community.This paper also examines a proposed knowledge sharing framework to get it adapted for the senior citizens community.